2020
DOI: 10.1126/sciadv.abd2520
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired high-power-density strong contractile hydrogel by programmable elastic recoil

Abstract: Stimuli-responsive hydrogels have large deformability but—when applied as actuators, smart switch, and artificial muscles—suffer from low work density due to low deliverable forces (~2 kPa) and speed through the osmotic pressure–driven actuation. Inspired by the energy conversion mechanism of many creatures during jumping, we designed an elastic-driven strong contractile hydrogel through storing and releasing elastic potential energy in polymer network. It can generate high contractile force (40 kPa) rapidly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 48 publications
4
91
0
Order By: Relevance
“…Apart from the above-mentioned application practices, hydrogels could be also extended to other biomedical fields, such as tissue fillers, 393 bioimaging, 394 biosensor, 395 conductive wearable/implantable biodevices, 66 , 67 soft robots, 396 etc. Hydrogel products used for cosmetic filler have been widely reported and evaluated, where HA gel is the mostly used.…”
Section: In Vitro and In Vivo Potential Applications Of Hydrogelmentioning
confidence: 99%
“…Apart from the above-mentioned application practices, hydrogels could be also extended to other biomedical fields, such as tissue fillers, 393 bioimaging, 394 biosensor, 395 conductive wearable/implantable biodevices, 66 , 67 soft robots, 396 etc. Hydrogel products used for cosmetic filler have been widely reported and evaluated, where HA gel is the mostly used.…”
Section: In Vitro and In Vivo Potential Applications Of Hydrogelmentioning
confidence: 99%
“…In the engineering field, hydrogel films also These tough hydrogels are not stale at redox conditions that transform Fe 3+ ions to Fe 2+ ions having poor capacity to form robust coordination bonds with carboxyl groups. [37,38] To address these issues, it is highly desired to seek another kind of metal-coordination complexes that are robust, colorless, and compatible with the radical polymerization, i.e., stable in pregel solution and little influence on polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it has been reported that photo-sensitive coordinate bonds can efficiently release the energy stored by the hydrogel. 128 The authors took poly(acrylamide-co-acrylic acid) (P(AAm-co-AAc)) hydrogel for illustration. After being prestretched and immersed in Fe 3+ solution, the deformation of hydrogel is fixed by the coordinate bonds between Fe 3+ and carboxyl groups from AAc units which temporarily store potential energy in hydrogels.…”
Section: Light-responsive Polymer Networkmentioning
confidence: 99%
“…After UV irradiation, Fe 3+ is reduced to Fe 2+ , resulting in the breakdown of the coordinate bonds and the fast release of the elastic potential energy stored in the hydrogel. 128 This strategy of storing and releasing elastic energy, based on the destabilization of the coordination bonds by photoreduction, endows hydrogels with an elasticity-plasticity switchability, multi-stable deformability in fully reversible and programmable manners, and anisotropic or isotropic deformations. With the high power density and programmability via this customizable modular design, these hydrogels demonstrated potential for broad applications in artificial muscles, contractile wound dressing, and high-power actuators.…”
Section: Light-responsive Polymer Networkmentioning
confidence: 99%